Modification of Aβ Peptide Aggregation via Covalent Binding of a Series of Ru(III) Complexes - Gomes, Luiza M. F. (Front Chem, 2019)
Alzheimer's disease (AD) is the most common form of dementia, leading to loss of cognition, and eventually death. The disease is characterized by the formation of extracellular aggregates of the amyloid-beta (Aβ) peptide and neurofibrillary tangles of tau protein inside cells, and oxidative stress. In this study, we investigate a series of Ru(III) complexes (Ru-N) derived from NAMI-A in which the imidazole ligand has been substituted for pyridine derivatives, as potential therapeutics for AD. The ability of the Ru-N series to bind to Aβ was evaluated by NMR and ESI-MS, and their influence on the Aβ peptide aggregation process was investigated via electrophoresis gel/western blot, TEM, turbidity, and Bradford assays. The complexes were shown to bind covalently to the Aβ peptide, likely via a His residue. Upon binding, the complexes promote the formation of soluble high molecular weight aggregates, in comparison to peptide precipitation for peptide alone. In addition, TEM analysis supports both amorphous and fibrillar aggregate morphology for Ru-N treatments, while only large amorphous aggregates are observed for peptide alone. Overall, our results show that the Ru-N complexes modulate Aβ peptide aggregation, however, the change in the size of the pyridine ligand does not substantially alter the Aβ aggregation process.